2002
DOI: 10.1104/pp.000810
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Auxin, pH, and Stress in the Activation of Embryogenic Cell Division in Leaf Protoplast-Derived Cells of Alfalfa

Abstract: Culturing leaf protoplast-derived cells of the embryogenic alfalfa (Medicago sativa subsp. varia A2) genotype in the presence of low (1 m) or high (10 m) 2, 4-dichlorophenoxyacetic acid (2,4-D) concentrations results in different cell types. Cells exposed to high 2,4-D concentration remain small with dense cytoplasm and can develop into proembryogenic cell clusters, whereas protoplasts cultured at low auxin concentration elongate and subsequently die or form undifferentiated cell colonies. Fe stress applied at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
222
0
17

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(257 citation statements)
references
References 70 publications
18
222
0
17
Order By: Relevance
“…This aspect has been investigated by Johri and D'Souza (1990) and these studies quite unexpectedly indicated that the responsiveness of cells to auxin can be modulated by medium pH and nutrient level. A similar role of auxin, pH and stress in the formation of embryogenic cell type has since been found in the leguminous plant Medicago sativa (Pasternak et al, 2002).…”
Section: Auxin Regulation Of Caulonema and Protonemal Rhizoid Differesupporting
confidence: 61%
“…This aspect has been investigated by Johri and D'Souza (1990) and these studies quite unexpectedly indicated that the responsiveness of cells to auxin can be modulated by medium pH and nutrient level. A similar role of auxin, pH and stress in the formation of embryogenic cell type has since been found in the leguminous plant Medicago sativa (Pasternak et al, 2002).…”
Section: Auxin Regulation Of Caulonema and Protonemal Rhizoid Differesupporting
confidence: 61%
“…Picloram has been successfully employed for the induction of friable embryogenic calli in root and tuber crops, especially cassava, sweet potato, and yam (Nyaboga et al 2013;Triqui et al 2008;Belarmino and Gonzales 2008). The copper sulfate used in the media combination with auxins creates oxidative stress conditions that promote both cell division and embryogenic cell formation, as reported by Pasternak et al (2002).…”
Section: Effect Of Different Concentrations Of Picloram Supplemented mentioning
confidence: 75%
“…Indeed, many of the same players that have been implicated in left-right asymmetry (K ϩ channels, plasma membrane H ϩ flux, cell membrane transporters, and gradients of serotonin/auxin, regulatory roles of pH, fusicoccin, etc.) are now known to be crucial components of auxin signaling (Arend et al, 2002;Coenen et al, 2002;Pasternak et al, 2002;Hager, 2003;Rober-Kleber et al, 2003;Wind et al, 2004). As with serotonin, there is thought to be a soluble auxin receptor (Dharmasiri et al, 2003;Woodward and Bartel, 2005a,b).…”
Section: Comparison To Other Morphogen Gradientsmentioning
confidence: 99%